Канонічна форма відносно напівскалярної еквівалентності матричної в'язки з невиродженою першою матрицею - Прокіп, В.М. (Український математичний журнал, 2011)
Многочленные (n×n)-матрицы A(x) и B(x) над полем F называются полускалярно эквивалентными, если существуют неособенная (n×n)-матрица P над F и обратимая (n×n)-матрица Q(x) над F[x] такие, что A(x)=PB(x)Q(x). Приведена каноническая форма относительно полускалярной эквивалентности для матричного пучка A(x)=A₀x−A₁, где A₀ и A₁ — (n×n)-матрицы над полем F и A₀ — неособенная матрица. Polynomial matrices A(x) and B(x) of size n×n over a field F are called semiscalar equivalent if there exist a nonsingular n×n matrix P over F and an invertible n×n matrix Q(x) over F[x] such that A(x)=PB(x)Q(x). We give a canonical form with respect to the semiscalar equivalence for a matrix pencil A(x)=A₀x−A₁, where A₀ and A₁ are n×n matrices over F, and A₀ is nonsingular.